Chapter Il fascismo 'liberista' e la 'quasi abolizione' dell'imposta di successione del 1923 - Gabbuti, Giacomo (Studi e saggi, 2021)
In summer 1923, in the midst of the 'fight' to balance the budget, Minister Alberto De Stefani announced the abolition of inheritance tax, pursuant to the 'full powers' granted to the government by the Parliament. This abolition - possibly the most iconic act of the 'financial restauration' carried on by De Stefani - provoked surprise and interest in the country and abroad but was substantially overlooked by historians. This chapter - first outcome of a research in progress - offers a first historical reconstruction of this episode of early 1920s Italian economic history, by documenting both the positions of an influent advisor of De Stefani, the economist Maffeo Pantaleoni, and even more, the lobbying activity carried on by pressure groups such as the bankers' association, an influential businessman linked to Mussolini such as Cesare Goldmann, and a young, very proactive association of notaries. Moreover, the chapter surveys the way in which both Italian and international media reported on this case of politics of inequality, offering a different perspective on a crucial period in the consolidation of Fascist power.